Recognition of Pleuropterus angulatus (Polygonaceae) as a separate species: evidence from morphological and molecular data - Wen, Gui-Hua; Yang, Jing-Yu; Hu, Hui; Li, Jian-Hua; Xu, Bing-Qiang (Phytotaxa, 2024)
On the basis of morphological and molecular data, we demonstrate that Polygonum multiflorum var. angulatum actually belongs to the genus Pleuropterus. As a consequence, a nomenclatural change (Pleuropterus angulatus comb. et stat. nov.) is proposed. This species is closely related to Pleuropterus multiflorus, but differ from the latter in root tuber color (white vs. yellow-brown in P. multiflorus), vascular strands (absent vs. present), branchlets (densely papillate vs. smooth), and vein (densely papillae vs. non-papillate), and extra-floral nectaries (deeper, thicker around the lips vs. shallow, thin).